Ultrasound assisted acidification of model foods: Kinetics and impact on structure and viscoelastic properties - Miano A.C. (2017)
This work was supported by the São Paulo Research Foundation (FAPESP, Brazil) [grant numbers 2014/16998-3 (project), 2014/26433-3 (JC Pereira B.Sc. scholarship)]; the National Council for Scientific and Technological Development (CNPq, Brazil) [grant number 401004/2014-7 (project) and B Miatelo B.Sc. scholarship (PIBIC)]; and the “Consejo Nacional de Ciencia, Tecnología e Inovación Tecnológica” (CONCYTEC, Perú) [grant number 272-2015-FONDECYT (A.C. Miano Ph.D. scholarship)].